Comparison of Nata Quality From Cassava Peels (Manihot esculenta), Ladyfinger Bananas Peels (Musa acuminata Colla), and Durian Peels (Durio zibethinus) - Mashuri Masri; Irhamniah Irhamniah; Ulfa Triyani A Latif; Rusny Rusny (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract : Agricultural waste is composed of carbohydrates which can be be used as a growth medium for bacteria Acetobacter xylinum to produce fermented products in the form of nata. Producing nata from fruit waste such as Cassava peels (Manihot esculenta), Ladyfinger bananas peels (Musa acuminata Colla) and Durian peels (Durio zibethinus) is one of the efforts to reduce environmental pollution. This study aims to compare the quality of nata from Cassava peels (endodermis), Ladyfinger bananas peels (endodermis) and durian peels (endodermis) based on the gel thickness, nata yield and organoleptic test. From the results of the study concluded that Durian peels and Ladyfinger bananas peels could be used as an essential ingredient in making nata. Nata de durio is the best nata product in terms of thickness, nata yield and organoleptic tests. Meanwhile Cassava peels cannot be used as raw material for making nata.Abstrak : Limbah pertanian terdiri dari karbohidrat, yang dapat digunakan sebagai media pertumbuhan bagi bakteri Acetobacter xylinum untuk menghasilkan produk fermentasi dalam bentuk nata. Memproduksi nata dari limbah buah seperti kulit ubi kayu (Manihot esculenta), kulit pisang Ladyfinger (Musa acuminata Colla), dan kulit Durian (Durio zibethinus) adalah salah satu upaya untuk mengurangi pencemaran lingkungan. Penelitian ini bertujuan untuk membandingkan kualitas nata dari kulit ubi kayu (endodermis), kulit pisang emas (endodermis), dan kulit durian (endodermis) berdasarkan ketebalan gel, rendemen nata, dan uji organoleptik. Hasil penelitian menyimpulkan bahwa kulit Durian dan kulit pisang emas dapat digunakan sebagai bahan penting dalam membuat nata. Nata de durio adalah produk nata terbaik dari segi ketebalan, rendeman, dan uji organoleptik, sedangkan kulit ubi kayu tidak dapat digunakan sebagai bahan baku pembuatan nata.